(3JYdjbI Ydi GdebUO GdCbUi hGdeWdH GdCSfi ebOeIs - (3GdMSjfj, aNQ GdOjf, eMeO Hf MSjf, J HYO (B968(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg GdZahQ GdQMje(B...(3bGd GdeU WGH KQGg GdebUO GdKGdK aj EKHGJ GdUGfY(B...s
(3BNQgG (B:s
...(3bhdg CfJ GdEeGe GdPj JQLh HWGYJg, bhdg jhe GdfLGIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B249s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds